PROGRAM PENGABDIAN MASYARAKAT TERPADU (PPMT) PENINGKATAN POTENSI DESA GONDANG DENGAN PEMBENTUKAN KOPERASI - lilik andriyani; Fani Riski Arbani; Faridatul Kudsiyah; Angke Diasi Iswarianti; Nur Lailia Ulinnuha; Ilma Filiana (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
The potential of Gondang Village, which has natural resources, is quite good, and most of its inhabitants are farmers. Most of the farmers in Gondang village are elderly. They experience difficulties in terms of access to long distances and access to the procurement of fertilizers, mostly subsidized fertilizers, agricultural medicines, and others, and limited knowledge of farmers. Although a small number of youth farmer groups who are members of